Everything you need to know about organic foods - Dunn-Georgiou, Elisha (New York : Rosen Pub. Group, 2002)
Discusses the organic food movement and recent information about the United States Department of Agriculture's criteria for what defines an organic food.
Includes bibliographical references (p. 61) and index.
First year to Fourth year students
Keywords: Natural foods -- Juvenile literature; Organic gardening -- Juvenile literature; Natural foods; Organic gardening